THE MEANING OF SCHOOL COUNSELORS’ PRESENCE FOR STUDENTS EXPERIENCING ACADEMIC ANXIETY: A PHENOMENOLOGICAL STUDY IN CENTRAL LOMBOK VOCATIONAL SCHOOLS - Eliza Pertiwi, Rizka (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Academic anxiety is a common emotional challenge among vocational students who face dual academic and vocational demands, often resulting in decreased motivation, impaired concentration, and lower academic performance. School counselors play a crucial role in supporting students experiencing academic anxiety, yet limited research has examined how students themselves interpret the presence of school counselors in this context. This phenomenological study explores the lived experiences and perceived meaning of the presence of guidance and counseling (BK) teachers among students with academic anxiety in three private vocational schools in Central Lombok, Indonesia. Using purposive sampling, data were collected from 10 students identified with moderate to high academic anxiety, three school counselors, and two homeroom teachers through in-depth interviews, observations, and document analysis. Data were analyzed using the phenomenological procedures of Miles and Huberman, involving coding, thematic categorization, comparison of experiences, and theoretical integration. Four major themes emerged: (1) school counselors as an emotional safe space, (2) providers of academic coping strategies, (3) motivators who enhance students’ confidence, and (4) mediators connecting students, teachers, and parents. These findings highlight that the presence of school counselors extends beyond administrative functions and is deeply experienced as emotional, motivational, and relational support. The study underscores the critical role of counselor–student interpersonal relationships in reducing academic anxiety, particularly within vocational school settings. Implications include the need for strengthened counseling programs, proactive interventions, and enhanced counselor training to better address academic anxiety and foster student resilience.